Phylogenetic relationships of Strongyloides species in carnivore hosts. (October 2020) - Ko, Phoo Pwint; Suzuki, Kazuo; Canales-Ramos, Marco; Aung, Myo Pa Pa Thet Hnin Htwe; Htike, Wah Win; Yoshida, Ayako; Montes, Martin; Morishita, Kazuhiro; Gotuzzo, Eduardo; Maruyama, Haruhiko; Nagayasu, Eiji
Abstract: Strongyloides stercoralis is a parasitic nematode and a major pathogen responsible for human strongyloidiasis. The presence of this species in the dog population has led to an interest in studying the phylogenetic relationships among Strongyloides spp. in carnivore hosts. In the present study, Strongyloides spp. from various carnivore hosts (raccoon, Japanese badger, Siberian weasel, raccoon dog, masked palm civet, and domestic cat) were sought. Except for civets, Strongyloides spp. were identified in all host species. Based on 18S rDNA sequences, nine OTUs (operational taxonomy units) were identified. Molecular phylogenetic analyses using 18S28S rDNA and mitochondrial cox1 (cytochrome c oxidase subunit 1) sequences clustered them into two groups. The first group (named the stercoralis / procyonis group) was comprised of six OTUs and occurred in cats, raccoon dogs, raccoons ( S. procyonis ), Siberian weasels, and Japanese badgers and included S. stercoralis from humans and dogs. The second group (named the planiceps group) was made up of Strongyloides spp. from raccoon dogs (two OTUs) and one OTU from Siberian weasels. Subsequent analysis using almost the full-length nucleotide sequences of protein-coding genes in their mitochondrial genomes placed Strongyloides spp. of cats in a sister taxon position to S. stercoralis, whereas S. procyonis from raccoons was more distantly related to them. The presence of Strongyloides spp. from various carnivore hosts, which are close relatives of S. stercoralis, suggests this group of Strongyloides (the stercoralis / procyonis group) essentially evolved as parasites of carnivores, although more data on Strongyloides spp. from primate hosts are needed. Graphical abstract: Unlabelled Image